Vertically oriented ZrO2[sbnd]TiO2[sbnd]Nb2O5[sbnd]Al2O3 mixed nanopatterned bioceramics on Ti6Al7Nb implant assessed by laser spallation technique - Rafieerad, A.R.; Bushroa, A.R.; Nasiri-Tabrizi, B.; Crum, R.; Gámez, C.; Vadivelu, J.; Gupta, V. (Elsevier, 2017)
Recently, reports on the fabrication of nonstructural configuration have generated scientific interest due to increased awareness of the oxide nanotubes in the biomedical implant field and other industrial approaches. Here, highly ordered ZrO2[sbnd]TiO2[sbnd]Nb2O5[sbnd]Al2O3 nanotube arrays were grown by physical vapor deposition (PVD) of a zirconium layer on titanium-niobium alloy implant (IMPTi67) and succeeding anodic oxidation at a constant voltage (60 V) with exposure times ranging from 30 to 300 min. To crystallize the resulting mixed oxide nanotubes, heat treatment was also applied. The nanotubes were placed in an atmospheric furnace at temperatures ranging from 450 to 800 °C for 2 h. This treatment provided a morphological evolution was strongly influenced by the anodization time, where highly aligned bamboo-shaped oxide nanotubes (161 ± 44 nm in inside diameter and ∼1 μm in length) were formed after 300 min of anodization. After annealing at temperature below 500 °C, the nano-array configuration remained stable and the average inner diameter decreased to around 40 nm. The effects of anodically fabrication time on the adhesion strength of four-phase multilayered mixed oxide nanotubes on anodized Zr/IMPTi67 surfaces assed by microscratch analysis. From the results, increasing the annealing temperature further to 800 °C fully destroyed the nanotubes and consequently the tubular arrangement was converted to a coarse grain structure. It was revealed that annealing at 450 °C for 2 h was the optimum conditions for stable nanotubular array generation, where the highest adhesion strength (shifted from 2595.59 to 2640.12 mN), microhardness (372 HV) and hydrophilicity (15 ± 1°) were recorded. It is notify that the adhesion strength of highly ordered mixed nanotubes was remarkably decreased after thermal treatment at 800 °C (1817.51 mN). Through the laser spallation analysis, the intrinsic adhesion strength of the Zr/IMPTi67 interface was found to be at 63 MPa, while the first stages of failure occurred at a stress state of 35 MPa. The adhesion of the film with the tubular structure proved to have a significantly larger adhesion strength of 246 MPa for the complete failure and 203 MPa for incipient stages of spallation. The considered surface modification can be an effective step in determining the interface strength between biomedical implants and the nanostructured coatings.